Integrated research-based learning model through environmental exploration: A strategy for improving students' scientific article writing skills - Riastuti, Reny Dwi; Aminah, Siti; Febrianti, Yuli; Rahmi, Rahmi (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2025)
The purpose of this study was to analyse the implementation of research article writing assignments in the Lower Plant Taxonomy course and evaluate its impact on the development of students' critical thinking and analytical skills, as well as scientific writing abilities. The model used was Research-Based Learning (RBL) integrated with field exploration (Nature Exploration). The method employed was a descriptive research approach, combining both quantitative and qualitative methods. The research sample consisted of 29 third-semester students in Biology Education, selected using a total sampling technique. Data were collected from the assessment of research article assignments based on RPS criteria, as well as semi-structured interviews with lecturers and students. Quantitative data were analysed descriptively, while qualitative data were analysed thematically to identify obstacles. The results showed that the implementation of RBL, structured in three phases (Exploration, Communication Interaction, and Reflection), was generally effective in improving competency. Most students, with an achievement rate of over 80%, achieved excellent performance, especially in the technical and structural aspects of writing, such as the preparation of the Research Methodology (92%) and the Suitability of the Bibliography (95%). However, significant obstacles were found in aspects that require critical analysis and in-depth argumentation, characterised by 17% of shallow Discussion errors and 13% of incomplete Data Analysis errors. Interviews confirmed that the main obstacles were limited guidance time, difficulty in determining original topics, and lack of confidence in developing theoretical arguments. The conclusion of this study confirms that PBR has successfully fostered research literacy and scientific attitudes. Its effectiveness needs to be improved through optimising guidance time, strengthening theoretical literacy, and providing special training to develop data analysis and argumentation skills. This model is relevant as an innovative curriculum for preparing prospective biology teachers who are reflective and research-oriented.